Geo-Chicago 2016 : geotechnics for sustainable energy : selected papers from sessions of Geo-Chicago 2016, August 14-18, 2016, Chicago, Illinois - Yesiller, Nazli; Zekkos, Dimitrios; Farid, Arvin; De, Anirban; Reddy, Krishna R. (Geotechnical special publication ;, 2016)
Contains 67 peer-reviewed papers on innovative ways of storing and extracting energy in and from geotechnical media and structures. Topics include: thermal geotechnics; geoenergy; mining wastes; energy geotechnics; offshore energy geotechnics; renewable energy; numerical and experimental modeling; and sustainable pavement solutions.